2019
DOI: 10.1532/hsf.2497
|View full text |Cite
|
Sign up to set email alerts
|

Poor Outcome of Surgical Management of Acute Malfunctioning Mechanical Mitral Valve During Pregnancy. Should Centers with Limited Resources Find Different Options?

Abstract: Background: Rheumatic heart disease (RHD) is the most common cardiac disease in pregnancy in developing countries with the mitral valve being the most affected. In this study, the results of surgical intervention in pregnant women presented with acute malfunctioning mechanical mitral valve were discussed. Methods: All patients underwent emergency redo mitral valve replacement due to acute malfunctioning mechanical mitral valve during pregnancy in a single center between January 2005 and December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Such findings were reported by other working groups in the country. Elsayed et al reported on 16 pregnant patients presenting with PVT with the majority (12 out of 16 patients) being either on LMWH or UFH, often in sub-therapeutic doses [Elsayed 2019]. The results of surgical intervention in their group of patients were comparable with ours, as they reported an early maternal mortality rate of 37.5% and a favorable fetal outcome in only 31.2% of the cases.…”
Section: E986supporting
confidence: 68%
“…Such findings were reported by other working groups in the country. Elsayed et al reported on 16 pregnant patients presenting with PVT with the majority (12 out of 16 patients) being either on LMWH or UFH, often in sub-therapeutic doses [Elsayed 2019]. The results of surgical intervention in their group of patients were comparable with ours, as they reported an early maternal mortality rate of 37.5% and a favorable fetal outcome in only 31.2% of the cases.…”
Section: E986supporting
confidence: 68%
“…Therefore, it is important to study the pathogenic mechanism and identify new therapeutic targets for RHD. To this end, the present study investigated the most common RHD, identified as mitral valve disease following review of the results of previous histopathological analyses (7). This finding led to the question: By which process is mitral valve disease directly associated?…”
Section: Introductionmentioning
confidence: 97%